Modified reinshaw and pollard criteria for a non-orthogonal cohesive natural interface intersected by an induced fracture - Sarmadivaleh, Mohammad; Rasouli, Vamegh (Springer, 2014)
Hydraulic fracturing is a widely used stimulation method to enhance the productivity of unconventional resources. The hydraulic fracturing operation in naturally fractured reservoirs or when it is expected to intersect a natural interface, such as an interbed is subjected to complexity.The induced fracture may cross, get arrested by or open the fracture plane upon its arrival at the natural interface. Besides other parameters, this depends on the natural interface mechanical properties, including the cohesion and friction angle of the interface. Several analytical criteria have been developed to predict the interaction mechanism of induced and natural fracture. Whilethese analytical solutions have been developed based on some simplified assumptions, they can provide a good understanding of the effect of different parameters. The first part of this paper summarizes the available criteria for interaction of hydraulic and natural fractures. Importantfactors will be mentioned and illustrations will be given to present the limitations of each criterion. The second part discusses the development and validation of an extension to Renshaw and Pollard criterion in the form a single analytical formula for non-orthogonal cohesive fracture. Thisincludes the contribution of the strength of the in-fill material to the bonding of the two sides of a fracture, hence its effect on the interaction mechanism. The proposed criterion was validated using published laboratory data. Finally, a methodology is proposed to help the design of interaction experiments in the laboratory, which can also be used for prediction of interaction mode in numerical simulations.